2018
DOI: 10.20944/preprints201812.0119.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processes of Direct Laser Writing 3D Nano-Lithography

Abstract: Direct laser writing three-dimensional nano-lithography is an established technique for manufacturing functional 3D micro- and nano-objects via non-linear absorption induced polymerization process. In this Chapter an underlying physical mechanisms taking place during nano-confined polymerization reaction, induced by tightly focused ultra-short laser pulses, are reviewed and discussed. The specialattention is paid on the effects that directly impact structuring resolution and minimum achievable feature size. An… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…When the wait time was introduced between exposures (on top of the mask rotation time) (Dome to Bullet, Bell to Pillar, Figure 2 F), the resulting microstructures became much taller with a nearly four times (Bullet; height 75 µm), and three times (Pillar; height 110 µm) increase, indicating much deeper SU-8 micro-pockets. This result is likely caused by the free-radical quenching during photopolymerization, as reported in previous studies [ 49 , 50 , 51 , 52 ]. We speculate that through the wait-time (on top of mask rotation time), the free radicals formed during the first exposure could have likely been quenched and reduced the number of free radicals present for further resist polymerization.…”
Section: Resultssupporting
confidence: 68%
“…When the wait time was introduced between exposures (on top of the mask rotation time) (Dome to Bullet, Bell to Pillar, Figure 2 F), the resulting microstructures became much taller with a nearly four times (Bullet; height 75 µm), and three times (Pillar; height 110 µm) increase, indicating much deeper SU-8 micro-pockets. This result is likely caused by the free-radical quenching during photopolymerization, as reported in previous studies [ 49 , 50 , 51 , 52 ]. We speculate that through the wait-time (on top of mask rotation time), the free radicals formed during the first exposure could have likely been quenched and reduced the number of free radicals present for further resist polymerization.…”
Section: Resultssupporting
confidence: 68%
“…This is of particular relevance for improved manufacturing of delicate structures. Experimental studies in this realm encounter serious challenges as it is not easy to control all parameters that influence the DLW process 27 or to observe this process on the nanoscale in operando. Additionally, difficulties in reliable fabrication of nanoscale specimens in combination with strain measurement complications make mechanical experiments challenging 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Direct Laser Writing (DLW) via 2 photon-polymerization (2PP), in which a laser beam is focused into a tiny volume which serves as a building block within UV-curable photoresists, can yield feature sizes below the diffraction limit of the excitation light. 11 Since the advent of the technology, research groups have strived to push the boundaries of achievable resolution and line width through innovative physical and chemical approaches. Kawata et al demonstrated the dramatic effects which could be achieved through the use of additional radical quenchers in the photoresist, which serve to minimize the extent to which created radicals can survive, thereby reducing the effective voxel volume.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-based direct-write technology using multiple photon absorption can allow spatial confinement of polymerization with minimal topological constraints. Direct laser writing (DLW) via 2-photon polymerization (2PP), in which a laser beam is focused into a tiny volume that serves as a building block within UV-curable photoresists, can yield feature sizes below the diffraction limit of the excitation light . Since the advent of the technology, research groups have strived to push the boundaries of achievable resolution and line width through innovative physical and chemical approaches.…”
Section: Introductionmentioning
confidence: 99%